2020
DOI: 10.3389/fchem.2020.00711
|View full text |Cite
|
Sign up to set email alerts
|

Cardanol and Eugenol Sourced Sustainable Non-halogen Flame Retardants for Enhanced Stability of Renewable Polybenzoxazines

Abstract: Olefin bonds participate in co-reaction with the benzoxazine functionality of the monomer and are one of the strategies used to affect the crosslink density of a polybenzoxazine network. In general, the double bond incorporation in starting material is usually catalyzed by expensive, rare earth metals affecting the sustainability of the reaction. The natural abundance of feedstocks with inherent double bonds may be a powerful platform for the development of novel greener structures, with potential applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…The larger surface area exhibited by such inter-connected system of voids alleviate altercation of heat and oxygen (air), which in turn contributes to an enhanced resistance against flame. Further, to improve the flame resistant behaviour of polymers, the same research group have reported [72] the introduction of hexacardanolphosphazene (CP) /hexaeugenolphosphazene (EP) as a flame retardant additives in to cardanol based tris-benzoxazine monomer (C-trisapm). The flame retardant properties of resulting matrices were studied using LOI, UL-94, and smoke density analysis.…”
Section: Cardanol Based Polybenzoxazines For Flame Resistant Applicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The larger surface area exhibited by such inter-connected system of voids alleviate altercation of heat and oxygen (air), which in turn contributes to an enhanced resistance against flame. Further, to improve the flame resistant behaviour of polymers, the same research group have reported [72] the introduction of hexacardanolphosphazene (CP) /hexaeugenolphosphazene (EP) as a flame retardant additives in to cardanol based tris-benzoxazine monomer (C-trisapm). The flame retardant properties of resulting matrices were studied using LOI, UL-94, and smoke density analysis.…”
Section: Cardanol Based Polybenzoxazines For Flame Resistant Applicationsmentioning
confidence: 99%
“…The flame retardant properties of resulting matrices were studied using LOI, UL-94, and smoke density analysis. Hexaeugenolcyclotriphosphazene (EP) was synthesized (Figure 4) as per the reported procedure [72] as follows; in a 250 mL RB flask comprising a mixture of acetonitrile and acetone (1:3 ratio) under N 2 atmosphere, K 2 CO 3 (143 mmol) was added. Eugenol (1.15 mmol) was dissolved in acetone and added to the above mixture, followed by the addition of N 3 P 3 Cl 6 (14.3 mmol).…”
Section: Cardanol Based Polybenzoxazines For Flame Resistant Applicationsmentioning
confidence: 99%
See 3 more Smart Citations